Automated CT perfusion imaging for acute ischemic stroke: Pearls and pitfalls for real-world use. (12th November 2019) - Vagal, Achala; Wintermark, Max; Nael, Kambiz; Bivard, Andrew; Parsons, Mark; Grossman, Aaron W.; Khatri, Pooja
Abstract : Recent positive trials have thrust acute cerebral perfusion imaging into the routine evaluation of acute ischemic stroke. Updated guidelines state that in patients with anterior circulation large vessel occlusions presenting beyond 6 hours from time last known well, advanced imaging selection including perfusion-based selection is necessary. Centers that receive patients with acute stroke must now have the capability to perform and interpret CT or magnetic resonance perfusion imaging or provide rapid transfer to centers with the capability of selecting patients for a highly impactful endovascular therapy, particularly in delayed time windows. Many stroke centers are quickly incorporating the use of automated perfusion processing software to interpret perfusion raw data. As CT perfusion (CTP) is being assimilated in real-world clinical practice, it is essential to understand the basics of perfusion acquisition, quantification, and interpretation. It is equally important to recognize the common technical and clinical diagnostic challenges of automated CTP including ischemic core and penumbral misclassifications that could result in underestimation or overestimation of the core and penumbra volumes. This review highlights the pitfalls of automated CTP along with practical pearls to address the common challenges. This is particularly tailored to aid the acute stroke clinician who must interpret automated perfusion studies in an emergency setting to make time-dependent treatment decisions for patients with acute ischemic stroke.